DIVERSIFIKASI MANAJEMEN KOPERASI SEKOLAH BERBASIS KEPEMIMPINAN TRANSFORMASIONAL DALAM MENINGKATKAN NILAI EKONOMI DAN EDUKATIF - Bunga Della Listinia; Nur Isnaini; Sefi Septianingsih; Siswadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Amidst demands to strengthen students' entrepreneurial character, school cooperatives should be a strategic space that generates not only economic value but also educational value. However, the reality on the ground shows that many school cooperatives are still managed conventionally, lack innovation, and have not optimally utilized the role of leadership. As a result, the cooperative's contribution to improving the school economy and student learning tends to stagnate. This study aims to analyze the role of diversified school cooperative management based on transformational leadership in enhancing economic and educational value. The study focuses on how a variety of innovative business units can be developed through leadership that inspires, motivates, and encourages the active participation of all cooperative members. The methodology used was library research, reviewing various sources such as books, scientific journals, and relevant previous research. The analysis was conducted using descriptive qualitative methods to gain a comprehensive understanding of the concept and its implementation. The results of the study indicate that diversified cooperative management, through the development of diverse and adaptive business units, can increase revenue and expand economic opportunities. Furthermore, transformational leadership plays a crucial role in fostering creativity, increasing student engagement, and building a culture of innovation. Thus, the integration of both is effective in strengthening the economic function while making cooperatives a meaningful learning tool.